O pós-estruturalismo e o lugar do “feminino”: o sexo, o jurídico e os “masculinismos” - de Fátima Cabral Barroso de Oliveira , Maria (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
In many ways, systems such as the legal ones reproduce “feminine” stereotypes and, therefore, questions related to gender and/or sexuality is not peripheral but central; even though feminist theories are erased and/or disregarded by systems they (re)think ways and theoretical concepts in a “reinvigorating” manner. Poststructuralist’s critique of the oppressive representational thought accomplished mainly in Foucault’s critique of power in a discourse and as a discourse and Irigaray’s critique on the phallocentric structure of thought are theoretical sources to understand how “masculine” representational systems can provide a place to the “feminine”, in order to (re)create new academic or legal worlds. How to deal with those questions when poststructuralist theories confirm the impossibility of the representation of the “feminine” in the Symbolic for all discourses are masculine?